Perceptions of relatives of critically ill patients for psychosocial support provided by the nurse in the Intensive Care Unit of the Guillermo Almenara Irigoyen Nacional Hospital - Reyes Tiburcio, Manuel (2019)
Objective: To determine the perceptions of relatives of critically ill patients on the psychosocial support providedby the nurse in the Intensive Care Unit of the Hospital Nacional Guillermo Almenara Irigoyen. Material andmethods: Study was descriptive and cross-sectional. The sample consisted of 50 family members of patientshospitalized in the ICU, determined by random probability sampling. Data collection was performed usinga questionnaire with 19 items, elavorado by the authors. Results: 64% of household favorably perceivedpsychosocial support provided by the nurse in the ICU and 36% perceived unfavorably. Regarding the emotionalaspect, it was found that the dimensions of understanding and tolerance in the visit, and listen to the family, 96%have a favorable perception of very favorable, likewise in the size of expressions of affection and support, 92%also have a favorable perception of very favorable. In the instrumental aspect, evidence that family members havea favorable perception of very favorable dimensions and additional information on specific needs, informationclearly and simply, and information on the diagnostic with 100%, 94% and 52% respectively. Regarding thesolution of specific problems, it is reported that 70% have a favorable perception of very favorable in the dimensionof family involvement in the care of the patient. By contrast, 60% have an indifferent perception in the dimension of information about requirements for blood replacement, and 50% have an unfavorable perception of a veryunfavorable in the dimension of flexibility in visiting relatives. Conclusion: It is concluded that the perceptionrelatives of critically ill patients on the psychosocial support provided by the nurse in the ICU is favorable.